Twenty Years of Airborne Water Vapor and Total Water Measurements of a Diode Laser Based Photoacoustic Instruments - Szakáll, Miklós; Mohácsi, Árpád; Tátrai, Dávid; Szabó, Anna; Huszár, Helga; Ajtai, Tibor; Szabó, Gábor; Bozóki, Zoltán (Frontiers in Physics, 2020)
We present relevant issues collected over twenty years of development and operation of an airborne water vapour / total water detector based on photoacoustic spectroscopy. The WaSulHygro instrument possesses high selectivity, short response time, and wide dynamic range, that are key requirements against trace gas measurement systems for applications in atmospheric sciences. Besides the major properties of WaSul-Hygro we discuss our efforts to develop a robust instruments that have proved its long-term reliability over the last fifteen years operating on-board a commercial aircraft within the framework of the CARIBIC project.2